Persepsi Konsumen Tentang Strategi Konten Promosi Iklan Flash Sale 12.12 Shopee - Mayang Riyantie; Alamsyah Alamsyah; Misnan Misnan (Brand Communication, 2022)
Flash Sale is one of the most effective types of advertising content strategies in communicating products and services, because flash sales are able to provide promotional messages with high appeal. This is in accordance with the desire and satisfaction of consumerism. This study aims to determine the response of shopee users regarding the promotional content of "Flash Sale 12.12 Shopee". The approach used is qualitative, by using descriptive method, with non-participant observation data collection. The results show that consumer perceptions of Shopee 12.12 flash sale ads are Shopee's strategy in influencing consumers to pursue low prices as soon as possible but in a short time. Audiences feel chased and encouraged to hunt for cheap items with fast transaction processes supported by free shipping costs. This strategy is trending very quickly, because consumers seem to be conditioned to double profits. With the frequency of flash sale shows that keep updating, even up to three times a day, consumers feel a loss if they miss the opportunity by not making a purchase.